Excessive Editing of Selfies on Social Media: The Illusion of Sustainability in Mental Health among Female Adolescents - Ismail, Abdelrahim Fathy (Journal of Ecohumanism, 2024)
The advent of social media has transformed how female adolescents perceive and present themselves, leading many to engage in excessive editing of their selfies. This practice is often seen as a means to boost their mental well-being by enhancing their self-image. However, this reliance on edited images may create a false sense of sustainability regarding their mental health. This study aims to explore the relationship between excessive selfie editing on social media and appearance-related anxiety in female adolescents. Employing a quantitative descriptive correlational design, the research involved 150 high school students, selected through a snowball sampling method, to examine the connection between their photo editing behaviors and psychological outcomes. Two validated instruments were utilized for data collection: the Selfie Editing Behavior Scale and the Appearance Anxiety Scale. Results indicated a significant positive correlation between the frequency of selfie editing and the levels of appearance anxiety experienced by the participants. These findings suggest that while adolescents may seek satisfaction through image enhancement, such practices can exacerbate insecurities and adversely affect their mental health over time.